Treatment Strategy for Revision Rhinoplasty in Asians - Jang, Yong Ju; Kim, Do-Youn (Facial Plastic Surgery, 2016)
Revision rhinoplasty in Asian patients is associated with problems related to the use of grafts or implant materials. Moreover, the septal cartilage of Asian individuals is generally weak and small, which makes it particularly vulnerable to injury or secondary deformity during primary surgery. Hence, there is an increased demand for major reconstruction of the septal cartilage framework during revision surgery in Asian patients. In revision rhinoplasty of the nose in Asian patients, appropriate management of the graft or implant is vital. The common problems resulting in the need for revision surgery include displacement, malposition, extrusion, recurrent inflammation, and infection of dorsally implanted alloplastic material. A short-nose deformity following silicone rhinoplasty is also a common problem that is difficult to manage. Furthermore, residual or recurrent deviation of the deviated nose, undercorrection of the convex nasal dorsum, and tip graft-related complications are frequently encountered problems that require revision. In revision rhinoplasty for Asian patients, autologous tissues, such as conchal cartilage and costal cartilage, play a pivotal role for use as a new dorsal implant or building block for major septal reconstruction. Therefore, it is imperative for surgeons to familiarize themselves with the appropriate use of autologous tissues, particularly costal cartilage.
Keywords: dorsal implant; major septal reconstruction; costal cartilage